2021
DOI: 10.3906/sag-1904-55
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thiol/disulfide homeostasis as oxidative stress marker in diabetic ketoacidosis

Abstract: The aim of present study was to investigate the dynamic thiol/disulfide homeostasis as oxidative stress marker in diabetic ketoacidosis (DKA). Materials and methods:A total of 77 participants consisting of 32 patients with DKA and 45 healthy volunteers were included in the study. Thiol/disulfide homeostasis (TDH) [total thiol-native thiol/disulfide changes] were measured in both groups (patient group and control group) using a brand new method developed by Erel and Neselioglu. Half of the difference between to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…When we compared mild and severe/critical groups in our study, we found that total thiol, native thiol, and disul de levels decreased signi cantly (Table 3). This decrease in disul de levels in patients with severe pneumonia was thought to be a result of the conversion of proteins to advanced oxidation products [34]. While IMA levels, one of the indicators of oxidative stress in COVID-19 patients, were found to be high in some studies, no signi cant increase was found in others [13,22,33].…”
Section: Discussionmentioning
confidence: 98%
“…When we compared mild and severe/critical groups in our study, we found that total thiol, native thiol, and disul de levels decreased signi cantly (Table 3). This decrease in disul de levels in patients with severe pneumonia was thought to be a result of the conversion of proteins to advanced oxidation products [34]. While IMA levels, one of the indicators of oxidative stress in COVID-19 patients, were found to be high in some studies, no signi cant increase was found in others [13,22,33].…”
Section: Discussionmentioning
confidence: 98%
“…Advanced oxidation in BS may show us the severity of the disease. Some studies have reported cases of advanced oxidation (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Disulfide structures (S-S), which are formed as a result of OS are reduced to thiol groups again, and thiol balance is achieved 12. In many studies, the measurement of dynamic thiol disulfide balance has been shown as an indicator of increased free radical levels in various diseases 13–16. The increase in OS causes free radical damage at the N-terminal end of albumin molecules and decreases the binding capacity of albumin.…”
Section: Introductionmentioning
confidence: 99%